2012
DOI: 10.1108/20441281211236562
|View full text |Cite
|
Sign up to set email alerts
|

The Essen Climate Evaluation Schema measure of social climate in a secure service for people with intellectual disabilities

Abstract: is based at the University of East Anglia, Norwich, UK. Cathy Thomas and Verity Chester are based at Partnerships in Care Learning Disabilities Service, Diss, UK. Abstract Purpose -The aim of the present study is to explore the psychometric properties of the EssenCES measure (patient report) of social climate in a secure sen/ice for people with intellectual disabilities. Design/methodology/approach -Patients (37men, 14 women. Mean age = 33.24 years, SD= 11.29, age range: 18-71 years) residing in a secure intel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 16 publications
5
14
1
Order By: Relevance
“…Overall reliability was sound (a = 0.87), although two subscales were lower than desired. Weight concern 4.3 (1.69) 0.5 6.0 0.90 Shape concern 4.8 (1.51) 0 was similar to other studies, more closely corresponding to scores from medium security settings (Milsom et al, 2014;Quinn et al, 2012). Nurses in this study also reported a slightly higher perception of Patient Cohesion and a much higher view of Experienced Safety.…”
Section: Nursessupporting
confidence: 85%
See 1 more Smart Citation
“…Overall reliability was sound (a = 0.87), although two subscales were lower than desired. Weight concern 4.3 (1.69) 0.5 6.0 0.90 Shape concern 4.8 (1.51) 0 was similar to other studies, more closely corresponding to scores from medium security settings (Milsom et al, 2014;Quinn et al, 2012). Nurses in this study also reported a slightly higher perception of Patient Cohesion and a much higher view of Experienced Safety.…”
Section: Nursessupporting
confidence: 85%
“…Consumers scored substantially higher in regard to Patient Cohesion and Experienced Safety, while the opposite was true for Therapeutic Hold. Relative to previous studies (Howells et al., ; Kerfoot et al., ; Milsom, Freestone, Duller, Bouman, & Taylor, ; Quinn, Thomas, & Chester, ; Schalast et al., ), consumers reported higher perceptions of Patient Cohesion and Experienced Safety. The mean consumer Therapeutic Hold subscale score was similar to other studies, more closely corresponding to scores from medium security settings (Milsom et al., ; Quinn et al., ).…”
Section: Resultscontrasting
confidence: 67%
“…Tighe & Gudjonsson 2 also reported this effect, as well as authors investigating social climate in secure settings. 16 , 17 A possible explanation for this is that medium secure wards represent the beginning of the care pathway accepting newly admitted patients and, as such, staff have had less opportunity to develop the knowledge of patients and therapeutic relationships necessary to achieve good relational security. As patients progress through the low secure and rehabilitation stages of the care pathway, this provides an opportunity for the components necessary to relational security to develop.…”
Section: Discussionmentioning
confidence: 99%
“…Quinn et al (2012) completed a preliminary investigation of the psychometric properties of the EssenCES with 51 patients within a secure intellectual disability service. The subscales and total score of the EssenCES demonstrated acceptable or good internal consistency.…”
Section: Introductionmentioning
confidence: 99%